Stimulation or lesion of the medial vestibular nucleus increases the number of choline acetyltransferase-positive efferent vestibular neurons in the brainstem. Issue 15 (17th October 2018) - Zhou, Yu-Juan; Zhao, Hao; Wang, Ying; Yu, Jing; Tian, Liang; Wang, Jing
Abstract : The vestibular center of the brainstem contains afferent and efferent vestibular neurons, which play an important role in information perception, processing, and sensory integration. Vestibular efferent neurons (VENs) can receive changes in vestibular afferent information and regulate peripheral vestibular function; however, it remains unclear how VENs change after vestibular afferent information increases or weakens. In this study, we used animal models with altered vestibular afferent information by electrically stimulating or destroying the vestibular medial nucleus (MVe). We confirmed the location of VENs in the brainstem by injecting five adult male Wistar rats in the vestibular region with a retrograde tracer. Following this, the MVe was stimulated electrically for 30 min in 20 naive rats. Rats were anesthetized and euthanized 1, 3, 6, and 12 h after stimulation. The MVe was electrolytically lesioned in another group ( n =20); then, the rats were anesthetized and euthanized 1, 3, 5, and 7 days after lesioning. VENs were clearly identified dorsolateral to the genu of the facial nerve (g7) in coronal brainstem sections using choline acetyltransferase (ChAT) staining. The number of ChAT-positive VENs dorsolateral to g7 increased significantly on both sides compared with the control group 3 and 6 h after electrical stimulation. The number of ChAT-positive VENs dorsolateral to g7 was significantly greater on both sides compared with controls 3 and 5 days after electrolytic lesion. In summary, we found that the number of ChAT-positive VENs was significantly increased following a change in the excitability of MVe neurons. This suggests that VENs can respond to changes in afferent vestibular information and feedback, and regulate the peripheral vestibule. In addition, this shows that acetylcholine is an important neurotransmitter that plays an important role in the perception and fine regulation of the vestibular system.